2015
DOI: 10.3390/s151229839
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Temperature-Sensing Behavior of Green and Red Upconversion Emissions from Stark Sublevels of Er3+

Abstract: Upconversion luminescence properties from the emissions of Stark sublevels of Er3+ were investigated in Er3+-Yb3+-Mo6+-codoped TiO2 phosphors in this study. According to the energy levels split from Er3+, green and red emissions from the transitions of four coupled energy levels, 2H11/2(I)/2H11/2(II), 4S3/2(I)/4S3/2(II), 4F9/2(I)/4F9/2(II), and 2H11/2(I) + 2H11/2(II)/4S3/2(I) + 4S3/2(II), were observed under 976 nm laser diode excitation. By utilizing the fluorescence intensity ratio (FIR) technique, temperatu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(21 citation statements)
references
References 27 publications
0
21
0
Order By: Relevance
“…From Equation (22), it can then be easily concluded that for a given energy gap, the most responsively detected temperature is Tnormalopt=12ΔE21kBin agreement with reported earlier findings. [ 112,204,242 ]…”
Section: Thermodynamic Perspective—optimization Of Thermometry With Tmentioning
confidence: 99%
See 1 more Smart Citation
“…From Equation (22), it can then be easily concluded that for a given energy gap, the most responsively detected temperature is Tnormalopt=12ΔE21kBin agreement with reported earlier findings. [ 112,204,242 ]…”
Section: Thermodynamic Perspective—optimization Of Thermometry With Tmentioning
confidence: 99%
“…in agreement with reported earlier findings. [112,204,242] So far, Equation ( 24) is still very specific for a certain choice of a luminescent ion, because it depends on the ion-related energy gap ΔE 21 . In order to become independent from any specific luminescent system and allow for general predictive guidelines, both the thermal response S a (T) and the relative sensitivity S r (T) can be normalized with respect to their values at T opt .…”
Section: Quantitative Guidelines For the Choice Of An Optimized Boltzmann Thermometermentioning
confidence: 99%
“…Besides temperature sensitivity, temperature accuracy δT is another parameter to characterize the optical thermometer, being estimated as 31,32…”
Section: Resultsmentioning
confidence: 99%
“…5(a)-(c), the red emission decreased when increasing the temperature from 20 to 100 C, which was in accordance with the classical theory of thermal quenching. 50 Quantitative temperature dependent intensity analysis in Fig. 5(c) shows that the Gd 2 O 3 -O 2 sample had better thermal stability than the Gd 2 O 3 -O 2 -free sample.…”
Section: Thermal Stabilitymentioning
confidence: 92%